(untitled) (International Journal of Studies in Nursing, 2020)
Introduction: Burnout is a psychological syndrome involving physical depletion, feelings of helplessness, negative self-concept, and negative attitudes towards work, life, and others. Burnout is a problem among health care professionals and nurses are found to be vulnerable. It is associated with a decrease in occupational well-being and increase in absenteeism, turnover and illness. Objectives: To evaluate the prevalence and factors associated with burnout among nurses at International Hospital Kampala (IHK). Methods: Analytical cross-sectional design was used. Data was collected from a sample of 120 nurses using questionnaire and Maslach Burnout Inventory (MBI) tools. Analysis was done using Statistical Package for Social Sciences and Microsoft excel. Results: The prevalence of burnout within the MBI subscales was highest in the subscale of personal accomplishment (PA) - 72.5%), followed by Depersonalization (DP) – 66.8% and Emotional Exhaustion (EE) -